Juveniles at the cross-roads reoffending-desistance. Role of mediation – example from Poland (Biuletyn Kryminologiczny, 2013)
Research on juveniles reoffending, especially in respect to restorative justice practices, are being led in certain countries regularly, in other not. Although the last is rather truth for Poland, longitudinal research on careers of former juveniles participating in mediation has been completed in 2013. Firstly, their reoffending has been checked in 1- 2,5 years period after mediation – then the percentage of reoffending was not high (14,4%), even if compared with research in other countries. Ten years after mediation, about one third (36, 2%) of former juveniles has been punished. Most of this part (40%) has committed single and less serious offense (there was more offenses against property). Only in 10% of the examined group criminality was intensified (however in their case there were risk factors – lack of profession or of work). Drop in number of sentenced persons after 24 year of age confirms the phenomenon of aging-out. Foreign research, even if some were evaluated as fragmentary or methodologically imperfect, are convincing, that taking part in mediation influences desistance, and even if not, less offenses are being committed and of less serious character. Results of Polish research, with two-third of those who succeed to desist offending and with high percentage of less serious offenses may support this thesis, however should be confirmed with more complex evaluation.